2023
DOI: 10.18178/ijiet.2023.13.11.1984
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Global World: A Case Study of Grammarly as e-Tool on ESL Learners’ Writing of Darul Uloom Nadwa

Sohaib Alam,
Mohammad Usama,
Md Moshabbir Alam
et al.

Abstract: Studies worldwide have explored how Grammarly as Electronic Tool (e-Tool) assists English as a Second Language (ESL) students in enhancing their writing. The present study aims to improve Madrasa ESL learners’ writing by minimizing inflectional morphemes related errors at Darul Uloom Nadwatul Ulama in Lucknow, Northern part of India. The study participants included sixty-eight Madrasa students who were enrolled in Alimiyat (equivalent to 12th) grade and were formed into two separate groups: an experimental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
“…Analyzing Facebook Mobile Usage: Efficacy and ESL Learners' Writing Proficiency for educational purposes. The research conducted by Alsayat [5], Noori et al [6], Yu and Wu [7], Muftah [8], Wang and Vásquez [9], Warschauer and Grimes [10], Alam et al [61], and Usama et al [62] showcases the transformative potential of these technologies in language pedagogy. Social networking sites are increasingly being seen as a viable option for learning English language writing skills due to their widespread use among the younger population.…”
mentioning
confidence: 99%
“…The efficacious adoption of the LMS can be impacted by various factors, including the stance of instructors and students, the technological infrastructure for information dissemination, and the backing of the establishment [12]. Instructors play a crucial part in determining if a learning management system is effective, successful, or ineffective [13]. In addition, studies have shown that the behavioral intention of teachers to utilize LMS in their classrooms is significantly associated with factors such as self-efficacy, the complexity of the technology, and subjective norms [14,15].…”
Section: A Web-based Instructionmentioning
confidence: 99%